2022
DOI: 10.1177/03000605211067749
|View full text |Cite
|
Sign up to set email alerts
|

Type B lactic acidosis associated with diffuse large B-cell lymphoma and the Warburg effect

Abstract: Type B lactic acidosis is a rare complication of non-tissue perfusion abnormalities caused by solid tumors or hematologic malignancies. Herein, we present the case of a 42-year-old man with type B lactic acidosis and hypoglycemia who was found to have a diffuse large B-cell lymphoma. The cause of lactic acidosis and/or hypoglycemia is thought to be the Warburg effect, which is when the metabolic rate of a rapidly growing malignant tumor is very high and dominated by glycolysis. Systemic damage from type B lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Unfortunately, plasma lactate was not consistently measured in these horses. Hyperlactatemia is a common cause of increased anion gap in horses and has been documented in human and canine lymphomas ( 28 , 29 ). Malignancy-induced lactic acidosis is suspected to be associated with the high metabolic rate of rapidly growing tumors and cancer metabolic reprogramming, resulting in hypoxia and increased glycolysis and thus lactate production by cancer cells, potentially exceeding the normal clearance rate of muscle and liver lactic acid ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, plasma lactate was not consistently measured in these horses. Hyperlactatemia is a common cause of increased anion gap in horses and has been documented in human and canine lymphomas ( 28 , 29 ). Malignancy-induced lactic acidosis is suspected to be associated with the high metabolic rate of rapidly growing tumors and cancer metabolic reprogramming, resulting in hypoxia and increased glycolysis and thus lactate production by cancer cells, potentially exceeding the normal clearance rate of muscle and liver lactic acid ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate from lactic acidosis secondary to malignancy is very high. Previously reported data showed that >70% of cases with lymphoma-associated Warburg effect died within 30 days [ 4 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among many others, malignancy is a known rare cause of type B lactic acidosis [ 2 ]. Moreover, the Warburg effect is an uncommon but serious condition that happens when neoplastic cells shift to aerobic glycolysis and it is highly linked to many cancers, particularly B-cell lymphomas [ 3 , 4 ]. It is considered an oncological emergency and is associated with poor prognosis and a high mortality rate if untreated [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lactic acidosis is the most common anion gap metabolic acidosis in critically ill patients [ 1 ]. It occurs when the production of lactic acid exceeds clearance [ 2 ]. Most of the lactate (80-90%) is cleared by the liver through gluconeogenesis while the remaining is cleared by the kidneys [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Type B lactic acidosis is most commonly seen with hematological malignancies, especially lymphomas. It is considered an oncological emergency and is associated with high mortality and poor outcomes if not treated promptly [ 2 ].…”
Section: Introductionmentioning
confidence: 99%